2019
DOI: 10.1155/2019/1793973
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Weather Conditions on the Onset of Spontaneous Pneumothorax in the Region of Sousse (Tunisia): Analysis of Time Series

Abstract: Introduction. Weather conditions were implicated in the onset of spontaneous pneumothorax (SP). Aim. Investigate the influence of weather conditions on the onset of SP. Methods. A total of 200 patients with SP in Sousse (Tunisia) were enrolled in the study between January 2010 and December 2014. An analysis of two time series (meteorological data and pneumothorax cases) was performed. Data on weather conditions were collected daily throughout the 5-year period. Results. A comparison of the mean temperature bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However, the results are contradictory. In fact, Park et al and Aissa et al 7,36 demonstrated a greater occurence of pneumothorax in warm versus cold seasons. Schieman et al and Motono et al 37,38 concluded that there was an www.nature.com/scientificreports/ absence of a significant link between pneumothorax and seasonality.…”
Section: Discussionmentioning
confidence: 95%
“…However, the results are contradictory. In fact, Park et al and Aissa et al 7,36 demonstrated a greater occurence of pneumothorax in warm versus cold seasons. Schieman et al and Motono et al 37,38 concluded that there was an www.nature.com/scientificreports/ absence of a significant link between pneumothorax and seasonality.…”
Section: Discussionmentioning
confidence: 95%